III Encontro Nacional dos MOVAs no III FME - (:unkn) unknown (My University, 2003)
Moacir Gadotti no III Encontro Nacional dos MOVAs no III FME.
Keywords: Instituto Paulo Freire; IPF; Paulo Freire; MOVA